KONFLIK BATIN TOKOH DALAM NOVEL MEMANG JODOH KARYA MARAH RUSLI - Valentari, Rinda Valentari; Jalil, Abdul Jalil; Rumadi, Hadi Rumadi (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2015)
ABSTRAK: This study discusses the inner conflictsÂ of figureinnovel Memang Jodoh opus Marah Rusli. Discuss theinner conflict which occurs of each figure in novel Memang Jodoh opus Marah Rusli. In addition, this studyalsodiscusses from external factor and internal factor to evoked the inner conflicts offigure in novel Memang Jodoh opus Marah Rusli. This studyused a qualitative approachanddescriptivemethodthat aimstodescribe inner conflictsof figure in novel Memang Jodoh opus Marah Rusli to evoked by external factor and internal factor. The results ofthe research is aclassification ofinner conflicts of figurefound in novel Memang Jodoh opus Marah Rusli. The results ofthis studyalsoas a form ofdocumentationinner conflicts of figure in novel Memang Jodoh opus Marah Rusli. Keywords: Inner confllicts, figure, the novel Memang Jodoh opus Marah Rusli.